2020
DOI: 10.1111/plb.13156
|View full text |Cite
|
Sign up to set email alerts
|

Pseudophoenix ekmanii (Arecaceae) seeds at suboptimal temperature show reduced imbibition rates and enhanced expression of genes related to germination inhibition

Abstract: Pseudophoenix ekmanii is a critically endangered palm species that can be found in the southeast of the Dominican Republic. The temperatures to which P. ekmanii seeds are exposed upon dispersal range from 32 to 23 °C (max and min) and can reach a low of approximately 20 °C in January. Our aim was to analyse the effect of suboptimal (20 °C) and optimal (30 °C) germination temperature on seed imbibition, moisture content, embryo growth and gene expression patterns in this tropical palm species. Seed imbibition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…One possible reason for the presence of dormancy in desiccation-sensitive Arecaceae seeds can be ascribed to the fact that a wet soil surface alone does not ensure germination success. Seeds also have a hightemperature requirement (c. 25-40 °C, with 30 °C being optimal for many species) to germinate, and this temperature range occurs in the tropical rainforest all year (Broschat 1998;Hussey 1958;Rees 1962;Visscher et al 2020). However, soil temperature increasing to 40-60 °C is a common occurrence, and such "erratic" high temperatures on the soil surface have a risk of drying the seeds.…”
Section: Ecological Significance Of Dormancy In Desiccation-sensitive Arecaceae Seedsmentioning
confidence: 99%
“…One possible reason for the presence of dormancy in desiccation-sensitive Arecaceae seeds can be ascribed to the fact that a wet soil surface alone does not ensure germination success. Seeds also have a hightemperature requirement (c. 25-40 °C, with 30 °C being optimal for many species) to germinate, and this temperature range occurs in the tropical rainforest all year (Broschat 1998;Hussey 1958;Rees 1962;Visscher et al 2020). However, soil temperature increasing to 40-60 °C is a common occurrence, and such "erratic" high temperatures on the soil surface have a risk of drying the seeds.…”
Section: Ecological Significance Of Dormancy In Desiccation-sensitive Arecaceae Seedsmentioning
confidence: 99%
“…To date, transcriptome investigation has been scarcely applied in seed physiology since it was considered to provide only a partial understanding of the cellular events regulating seed dormancy alleviation or termination processes [ 27 , 28 ]. However, many recent contributions showed that, especially for species for which there is a lack of molecular data, transcripts composition analysis provides new insights on gene interactions and their regulatory mechanisms [ 29 , 30 , 31 ]. Microarray analysis showed that thermal oscillations elicited almost immediate large transcriptome changes in leafy spurge seeds exposed to alternating temperatures [ 5 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…With 2600+ species, palms constitute an essential component of tropical and sub-tropical biodiversity (Kissling et al 2019). The life cycle of long-lived palms starts with diaspores, which differ considerably in size, shape, and color (Broschat et al 2014;Corner 1966;Mabberley 2017;Tomlinson 1990). Typically, the dispersal unit of palms is a berry or fibrous drupe, which encompasses fibrous mesocarp, a thick endocarp, a fleshy nutritious endosperm, and a small embryo (Tomlinson 1990).…”
mentioning
confidence: 99%
“…The life cycle of long-lived palms starts with diaspores, which differ considerably in size, shape, and color (Broschat et al 2014;Corner 1966;Mabberley 2017;Tomlinson 1990). Typically, the dispersal unit of palms is a berry or fibrous drupe, which encompasses fibrous mesocarp, a thick endocarp, a fleshy nutritious endosperm, and a small embryo (Tomlinson 1990). It is well known (or inferred) that mostperhaps all-palm diaspores have an underdeveloped embryo, c. > 10% of the overall diaspore size, at the time of dispersal (Baskin and Baskin 2014b;Martin 1946;Tomlinson 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation